PROCESS ANALYSIS AND IMPACT OF PARTNERSHIPS BETWEEN COMPANIES AND NONPROFITS ON CSR PROGRAMS - Rodiannauli Pane; Dita Oki Berliyanti (International Journal Labs, 2024)
Indonesia regulates the initiation of social responsibility activities with the Limited Liability Company Law Number 40 of 2007. Initiation Corporate social responsibility activities or more popularly known as corporate social responsibility (CSR) is basically a need for corporations to be able to interact with local communities as a form of society as a whole. Corporate social responsibility activities will strengthen national development. Efforts to support sustainable development in some companies implement programs by synergizing with non-profit institutions. Companies and non-profit organizations enter into partnerships to provide joint solutions to various social problems in areas such as Health, Education and poverty alleviation. This study aims to see the important implications for the process and impact of partnerships that affect the sustainability of partnerships between companies and non-profit organizations. The research was conducted using qualitative research methods with the object of research on partnership programs that have been established between PT X and Non-Profit Institutions SMK TB, and PT Y with SMK SD. The results of this study revealed that partnership programs carried out by companies and schools have a positive impact on companies and schools. Although this partnership program makes the school unable to cooperate with other similar automotive companies, the positive impact obtained by the school is much more. In addition, students as beneficiaries also feel the positive impact of this partnership.